2011
DOI: 10.1371/journal.ppat.1002310
|View full text |Cite
|
Sign up to set email alerts
|

A Phenome-Based Functional Analysis of Transcription Factors in the Cereal Head Blight Fungus, Fusarium graminearum

Abstract: Fusarium graminearum is an important plant pathogen that causes head blight of major cereal crops. The fungus produces mycotoxins that are harmful to animal and human. In this study, a systematic analysis of 17 phenotypes of the mutants in 657 Fusarium graminearum genes encoding putative transcription factors (TFs) resulted in a database of over 11,000 phenotypes (phenome). This database provides comprehensive insights into how this cereal pathogen of global significance regulates traits important for growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
406
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 286 publications
(424 citation statements)
references
References 48 publications
16
406
2
Order By: Relevance
“…Similar efforts are underway for Magnaporthe oryzae (20). In a medium-scale approach, mutants in 657 transcription factor genes were used to construct a phenotype database for Fusarium graminearum (127). The foundations for high-throughput functional genomics have been established for T. reesei with a procedure for efficient construction of knockout mutants (111).…”
Section: High-throughput Transcriptomes and Functional Analysismentioning
confidence: 99%
“…Similar efforts are underway for Magnaporthe oryzae (20). In a medium-scale approach, mutants in 657 transcription factor genes were used to construct a phenotype database for Fusarium graminearum (127). The foundations for high-throughput functional genomics have been established for T. reesei with a procedure for efficient construction of knockout mutants (111).…”
Section: High-throughput Transcriptomes and Functional Analysismentioning
confidence: 99%
“…Several lytic enzymes and numerous other proteins involved in iron uptake, sterol trafficking, nitrate transport, and reactive oxygen species (ROS) production have also been linked to pathogenesis (reviewed in Walter et al, 2010). Recently 42 protein kinase genes and 62 transcription factor genes were found to be required for wheat head infection (Son et al, 2011;Wang et al, 2011). However, these studies have not provided a complete blueprint for pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study that systematically deleted all putative transcription factors (TFs) in this fungus found that many TFs are required for these primary fungal traits (Son et al, 2011b). In addition to the specific TFs, putative global regulators that are involved in the regulation of more diverse functions have also received attention.…”
Section: Introductionmentioning
confidence: 99%